Occupational factors for mood and anxiety disorders among junior medical doctors - Pougnet, Richard; Pougnet, Laurence; Kerrien, Margaux; Jousset, David; Loddé, Brice; Dewitte, Jean-Dominique; Garlantézec, Ronan (La Medicina del Lavoro, 2015)
Junior doctors are exposed to multiple occupational risks. The aim of this study was to assess the risk factors and protective factors for mood and anxiety disorders among junior doctors. Materials and methods: We conducted a cross-sectional study via an anonymous online questionnaire between October 2011 and June 2012. All the junior doctors in our faculty were included. The questionnaire inquired about demographic and health data. It contained four validated scales: the Center for Epidemiologic Studies Depression Scale (CES-D), the Spielberger anxiety questionnaire, the WHO quality of life (WHO - QOL) questionnaire and the Job Content Questionnaire. Finally, it sought to clarify the conditions of professional practice and the interactions between university programmes and junior doctorate students (change of specialty, pregnancy, leave of absence, etc.). Results: 192 juniors doctors participated in the study, 68.2% of whom were women. Out of the group, 13.0% presented a depressive syndrome, while 28.7% presented an anxiety disorder, 32.8% were experiencing Job Strain and 29.7% Iso Strain. The risk factor for anxiety was competition  between junior doctors: OR=4.23 (1.06‒16.82). The protective factors for mood disorders were the help provided by senior physicians and the respect shown by patients: OR=0.21 (0.06-0.74) and 0.20 (0.06-0.75), respectively. Conclusion: This study demonstrated the impact of the relationships with senior physicians and patients on junior doctors’ health at work. Consequently, prevention should not be focused uniquely on work organization, but should increase physicians’ awareness of the importance of this relationship.